Failure of acyclovir cream in treatment of recurrent herpes labialis. Issue 6487 (6th July 1985) - Shaw, M; King, M; Best, J M; Banatvala, J E; Gibson, J R; Klaber, M R
Abstract : A double blind, randomised, crossover placebo controlled trial of 5% acyclovir cream, applied topically five times a day for five days, was carried out in 45 patients with recurrent herpes labialis. These patients had a total of 72 episodes, 34 of which were treated with the 5% acyclovir cream and 38 with placebo cream. Treatment was begun by the patients as soon as possible after the onset of prodromal symptoms. There was no significant clinical benefit from treatment with acyclovir cream compared with placebo cream. The median healing times were nine days with acyclovir cream, 10 days with placebo cream, and 13 days when no treatment was given. The possibility that the 40% propylene glycol cream base alone has a therapeutic effect must therefore be considered.